Guillain-Barré Syndrome After Revision Lumbar Surgery: A Case Report - Rashid, Aymen (Cureus, 2017)
Guillain-Barré syndrome (GBS) is a term that is used to describe a group of immune-mediated peripheral neuropathies, with the most common feature being rapid polyradiculoneuropathy. The exact etiology of this syndrome is unknown. In the field of orthopedics, GBS has been reported to occur after total hip arthroplasty, orthopedic trauma, and spine surgery. We report a unique case of GBS after elective revision lumbar spine surgery. A 62-year-old female presented with persistent low back pain and radiculopathy and elected to have revision lumbar spine surgery. Approximately 24 to 36 hours after hospital discharge, she returned to the hospital with weakness in her legs. After an electromyography (EMG), the patient was diagnosed with GBS and placed on intravenous immunoglobulin (IVIG). She developed respiratory failure, which required intubation and eventually converted to a tracheostomy and was finally decannulated. Over the course of 12 months, she improved to her pre-surgical baseline, gaining 5/5 strength in her upper and lower extremities and was able to ambulate independently without any aids. This was a case of GBS that occurred in a patient approximately two weeks after revision lumbar surgery. GBS is a poorly understood and rare complication of lumbar spine surgery that needs to be recognized quickly to be effectively treated.